Pengembangan Modul Berbasis Realistic Mathematics Education (RME) Pada Materi Persamaan Kuadrat Untuk Siswa Kelas IX - Indah Sakinatul Khafifah; Arini Hidayati (CONSISTAN (Jurnal Tadris Matematika), 2025)
Because there was little contextual and engaging teaching materials, and students’ understanding of the material on quadratic equations was still low because of its abstract content, students’ motivation in learning this material was low. The purpose of this study was to create a mathematics learning module utilizing Realistic Mathematics Education (RME) for learning quadratic equations in the IX grade of junior high school and to find out the validity and feasibility of the learning module. This research was conducted in the Research and Development (R&D) method with the ADDIE development model, with the stages of Analysis, Design, Development, Implementation, and Evaluation. The subjects of the research were two validators, namely material validator and design validator and 17 students of the IX grade class of SMP Islam Nurul Hikmah Besuki. Research instruments used were validation quesnationnaries and questionnaries that were presented to the students. The results indicated that the developed module had material expert validity percentage of 81,67% and design expert validity percentage of 83,33%, both of which were very valid. Furthermore, the result of the practical test was 90,59% with very practical category. Based on the findings of this study, it can be proposed that the RME based module for the material quadratic equations is suitable to be applied in mathematics learning.